Implementasi Kepadatan Populasi dan Kombinasi Pemupukan melalui Daun pada Tanaman Buncis (Phaseolus vulgaris L.) - Erlin, Erlina Puspa Dewi; Mei Arini, Silvia Fitri (JURNAL AGROPLANT, 2022)
Beans is a legume vegetable that has benefits and is good for health, and is a rich source of protein. One of the efforts made to improve the quality of bean production is the provision of fertilizers that can support the growth and development of bean plants. Balanced fertilization results in higher returns in agriculture cultivation (Adam. 1987). Beans contain 2.4 g protein, 0.2 g fat, 7.7 g carbohydrates, as a source of calories and 6.5 g calcium, 4.4 g phosphorus, 1.1 g iron, 630 mg vitamin A, vitamins B1 0.08 mg, vitamin B2 0.01, vitamin B3 0.7 mg, vitamin C 1.90 mg, calories 35 cal and water content 89 grams which greatly affect the quality of public health (Waluyo and Djuria., 2013). This research was conducted from December 2021 to February 202, in Pancakarya Village, Ajung District, Jember Regency, East Java. This study used a factorial pattern consisting of two factors with four replications in a randomized block design (RAK). The first factor is population (P) which consists of a population (P1) 2 plants, and a population (P2) 3 plants. The second factor is the combination of fertilization (I) which consists of a combination of (I0) control, a combination of (I1) PSB Bacterial Culture + NPK Fertilizer, and a combination (I2) PSB Bacterial Culture + Complete Fertilizer. The collected data were analyzed by means of variance (Anova), if significantly different, then followed by BNT’s test of 5%. The result showed that the Population (P) dan Combination (I) treatments on the growth of plant height, number of branches, internode length, and weight fruit.